2010
DOI: 10.1021/ef100595e
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid-Salt-Based Complex Absorbents for CO2 Capture in a Membrane Contactor

Abstract: Phosphate or borate as an activating agent was added into the aqueous glycinate to form amino acid salt-based complex absorbents. Capture of CO2 by the complex absorbents was studied theoretically and experimentally using a hollow fiber membrane contactor. Reaction mechanism concerning the activation effect of phosphate and borate was presented theoretically. A mathematical model was developed to simulate mass transfer of the membrane contactor. The effects of absorbent and gas CO2 concentrations on mass trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…It can be seen that the surface tension follows the order: physical solutions<chemical solutions<amino acid salts<blended absorbents. The blend has the highest surface tension which is close to water (Lu et al, 2010a). Fu and Zhong (2010) found that the surface tension would follow a downward monotonic trend with increasing the temperature and the alcohol amine concentration.…”
Section: Absorbent Selectionmentioning
confidence: 91%
See 1 more Smart Citation
“…It can be seen that the surface tension follows the order: physical solutions<chemical solutions<amino acid salts<blended absorbents. The blend has the highest surface tension which is close to water (Lu et al, 2010a). Fu and Zhong (2010) found that the surface tension would follow a downward monotonic trend with increasing the temperature and the alcohol amine concentration.…”
Section: Absorbent Selectionmentioning
confidence: 91%
“…Lu et al (2005Lu et al ( , 2010Lu et al ( , 2010a) studied the absorption performance of blended solutions based on the amino and inorganic-amino acid salts in a hydrophobic microporous membrane. Lin et al (2008) used AMP with the activator PZ and found that with an increase in the additive concentration, the CO 2 absorption rate constantly improved.…”
Section: Absorbent Selectionmentioning
confidence: 99%
“…MGA is a promising, competitive and alternative to conventional (e.g., tower techniques) process. Relevant investigations on MGA have made significant progress [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…A good absorbent should be the liquid with high selectivity, good gas solubility, good reactivity, high absorption rate and high capacity, low volatility, low regeneration energy, no degradation, no corrosiveness [5]. It doesn't wet the membrane micropore in capture process [8]. Amine-based solvents and their blends as chemical absorbents are frequently used in MGA for CO 2 [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation